An energy efficient and self-healing 3-dimensional sensor cover. (14th January 2008) - Watfa, Mohamed K.; Commuri, Sesh
Wireless Sensor Networks (WSNs) promise a maintenance free, fault-tolerant platform for gathering different kinds of data. For widespread adoption of the wireless sensor technology, robustness in the event of abnormal behaviour is critical. In this paper, the coverage problem in a 3-dimensional space is studied. Due to node failures or node migration, some uncovered holes are created. The problem of a self-healing sensor network in the case of coverage holes is addressed through a back up scheme where a designated substitute set of sensor nodes is activated.